PROTECTION OF THE FUNDAMENTAL RIGHT TO WORK OF PEOPLE WITH INTELLECTUAL DISABILITIES:: A PROCEDURAL ANALYSIS (REMUNOM, 2025)
This research aims to explore the fundamental right to work for individuals with intellectual disabilities, analyzing the available procedural instruments for protecting this right. The chosen topic is justified by the social, legal, and economic relevance of including these individuals in the workforce. The research question addresses the suitable procedural instruments to safeguard the right to work for people with intellectual disabilities. The scientific hypothesis suggests that current procedural instruments are inadequate and proposes a participatory process model. The methodology includes theoretical and documentary research using deductive methods. It is concluded that a procedural system allowing direct participation of individuals with intellectual disabilities in decisions affecting them is necessary, highlighting the importance of collective processes and authorized representatives to ensure the effectiveness of labor rights for this population.